A Case Study of Family Knowledge About the Types Of Contraception Methods And Tools in The Family Planning Program - Citra Riyani (Newinera Publisher, 2020)
This study is to find out family knowledge about family planning (KB) and mothers want to do family planning program, to increase family knowledge about the types of methods and contraception. This research is a type of research with a case study design by conducting studies aimed at an information-gathering technique that is done by compiling a list of questions. The results showed two problems in the family, which were found in mothers who had not had a family planning age of 31 years and the age of the last child of 5 months. After a systematic review is made in determining the priority of the problem, health education is needed by the mother and family. The husband advised the mother to use contraception and only use natural contraception methods.